Bifurcation Diversity in an Annular Pool Heated from Below: Prandtl and Biot Numbers Effects (Communications in Computational Physics, 2018)
In this article the instabilities appearing in a liquid layer are studied numerically by means of the linear stability method. The fluid is confined in an annularpool and is heated from below with a linear decreasing temperature profile from theinner to the outer wall. The top surface is open to the atmosphere and both lateralwalls are adiabatic. Using the Rayleigh number as the only control parameter, manykind of bifurcations appear at moderately low Prandtl numbers and depending on theBiot number. Several regions on the Prandtl-Biot plane are identified, their boundariesbeing formed from competing solutions at codimension-two bifurcation points.